2018
DOI: 10.1007/s00436-018-5805-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carriers of Leishmania infantum in patients infected with human immunodeficiency virus (HIV) in Morocco

Abstract: In Morocco, visceral leishmaniasis (VL) is a parasitic disease caused by the flagellated protozoan parasite Leishmania infantum. L. infantum is transmitted by the bite of female phlebotomine sandflies, and its main reservoir hosts are domestic dogs. Asymptomatic infection with L. infantum is more frequent than clinically apparent disease. In HIV-infected patients, the risk of clinical VL is increased due to immunosuppression that may reactivate latent infections. However, coinfected subjects do not necessarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Recently, in a systematic review of asymptomatic visceral leishmaniasis in the Indian subcontinent, Hirve et al [29], including 31 articles with different tests (rK39 immunochromatographic test, rK39 ELISA, DAT, PCR or Leishmanin skin test), found a prevalence from 0.25% to 36.9%, depending on the method used. Recently, Echchakery et al [18], in Morocco, found a prevalence of 5% in PLWH by indirect immuno uorescence. Clearly, there is no consensus about the best diagnostic tool to estimate the frequency of asymptomatic Leishmania infection in the population, and in the context of HIV infection, even in fully developed symptomatic disease, there are few data from Latin America regarding the performance of diagnostic methods [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in a systematic review of asymptomatic visceral leishmaniasis in the Indian subcontinent, Hirve et al [29], including 31 articles with different tests (rK39 immunochromatographic test, rK39 ELISA, DAT, PCR or Leishmanin skin test), found a prevalence from 0.25% to 36.9%, depending on the method used. Recently, Echchakery et al [18], in Morocco, found a prevalence of 5% in PLWH by indirect immuno uorescence. Clearly, there is no consensus about the best diagnostic tool to estimate the frequency of asymptomatic Leishmania infection in the population, and in the context of HIV infection, even in fully developed symptomatic disease, there are few data from Latin America regarding the performance of diagnostic methods [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to evaluate the magnitude of this problem in other areas where asymptomatic immunosuppressed individuals can progress to symptomatic disease more frequently, with poor therapeutic outcomes and a high rate of relapse [13,[15][16][17]. Another important point is that PLWH could be asymptomatic carriers of Leishmania and only develop symptoms in the presence of severe immunosuppression, maintaining the transmission cycle of transmission in areas without other mammalian reservoirs [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…What is more, we must keep in mind that 17% of the leishmaniasis cases in the Fuenlabrada outbreak involved some degree of immunosuppression [26] and that two of the three immunosuppressed patients studied in the present work were infective for sand flies. In Morocco, L. infantum has been detected in the 3% of HIV-coinfected asymptomatic patients by direct microscopic examination of smears of buffy-coat cells stained with May-Grünwald Giemsa [27] and in Italy, L. infantum DNA is present in 16.5% of HIV-infected asymptomatic patients [28]. On the other hand, it is necessary to draw attention to the fact that these patients are not systemically ill and may remain untreated for long periods, in the meantime being potentially infectious to sand flies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Latent infection of VL in HIV-infected patients has been noticed, so people living with HIV have a high risk of VL progression when Leishmania -infected. 8 This point could be better explored, because if patients present a decrease in CD4 + cell counts <200 cells/mm 3 , clinical manifestation of VL is more common. 9 …”
Section: Introductionmentioning
confidence: 99%